Things Fall Away : Philippine Historical Experience and the Makings of Globalization - Tadiar, Neferti Xina M. (Neferti Xina Maca), 1964- (Book collections on Project MUSE., 2009)
An argument that subaltern experiences that are devalued and overlooked in progressive late-twentieth-century Philippine literature have been essential to the social and economic changes wrought by globalization.